DEVELOPMENT OF GUIDED INQUIRY BASED WORKSHEET TO SUPPORT DIFFERENTIATED INSTRUCTION ON BUFFER TOPIC IN F PHASE OF SENIOR HIGH SCHOOL - Putri, Annisa; ‘Aini, Faizah Qurrata (STKIP PGRI Situbondo, 2024)
The Merdeka curriculum demand differentiated instruction in learning process. The implementation of differentiated instruction has not been well facilitated because there is no teaching material that suits the learning needs of students. Teachers need adequate teaching materials to facilitate the implementation of differentiated instruction. One of the teaching materials that can be applied by teachers is worksheet. The purpose of this research is to develop of guided inquiry based worksheet to support differentiated instruction. The type of research is Educational Design Research (EDR). The research instruments were self evaluation sheets, one to one sheets, validity and practicality questionnaires. Worksheet was validated by 5 validators was done by 9 students for the practicality test. The results showed that guided inquiry based worksheet to supporting differentiated instruction had an average validity of 0.88. This number correspond to valid category and a practicality level of 93% of students had very practical category. This research is recommended for further research in terms of effectiveness test in small groups, practicality and effectiveness in field tests.